The Effects of Cord Clamping Time and Early Skin-to-Skin Contact on Maternal Birth Satisfaction in Term Infants - KARAKOÇ, AYŞE (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Meeting the expectations of mothers during labor is defined as birth satisfaction. Evaluation of women's perception of satisfaction at birth is an important quality criterion in the evaluation of services. This study aims to determine the effect of cord clamping time and early skin contact on maternal birth satisfaction. Methods: Randomized controlled experimental study. The study data were collected between June and December 2018, from a total of 80 participants. Results: Case group was applied late cord clamping and skin contact, control group was applied routine care. The first breastfeeding time was 11.20 +/- 5.16 min. for the case group and 44.55 +/- 18.03 min. for the control group (p<0.001). Neonatal blood glucose levels within the first 15 minutes were 91.23 +/- 20.61 mg/dL for the case group and 83.13 +/- 14.17 mg/dL for the control group (p=0.044). Hemoglobin levels of the newborn 24 hours after birth were 18.90 +/- 1.58 g/dL for the case group and 18.13 +/- 1.78 g/dL for the control group (p=0.042). The difference between the before and after birth hemoglobin-hematocrit values of the mothers was not statistically significant (p=0.327 for Hgb; p=0.238 fot Htc). Postpartum satisfaction levels of the mothers were found to be 106.28 +/- 9.52 for the case group and 99.93 +/- 13.17 for the control group; mothers at the case group had higher postpartum satisfaction levels (p=0.016). Conclusion: Late cord clamping and early skin contact in newborn positively affect the first breastfeeding time, hemoglobin, hematocrit and blood sugar levels of newborns and can be considered as an important factor that increases mothers' satisfaction independent of many variables.
Keywords: Newborn; late cord clamping; skin to skin contact; maternal birth satisfaction; EXPERIENCE; WOMENS